Exposure to a Titanium Dioxide Product Alters DNA Methylation in Human Cells - Carlos Wells; Marta Pogribna; Arjun Sharmah; Angel Paredes; Beverly Word; Anil K. Patri; Beverly Lyn-Cook; George Hammons (Nanomaterials)
The safety of titanium dioxide (TiO2), widely used in foods and personal care products, has been of ongoing concern. Significant toxicity of TiO2 has been reported, suggesting a risk to human health. To evaluate its potential epigenotoxicity, the effect of exposure to a TiO2 product to which humans could be exposed on DNA methylation, a primary epigenetic mechanism, was investigated using two human cell lines (Caco-2 (colorectal) and HepG2 (liver)) relevant to human exposure. Global methylation was determined by enzyme-linked immunosorbent assay-based immunochemical analysis. Gene promoter methylation was evaluated using EpiTect Methyl II Signature PCR System Array technology. Expression of DNA methyltransferases, MBD2, and URHF1 was quantified by qRT-PCR. A decrease in global DNA methylation was observed in both cell lines. Across the cell lines, seven genes (BNIP3, DNAJC15, GADD45G, GDF15, INSIG1, SCARA3, and TP53) were identified in which promoters were methylated. Changes in promoter methylation were associated with gene expression. Results also revealed aberrant expression of regulatory genes, DNA methyltransferases, MBD2, and UHRF1. Findings from the study clearly demonstrate the impact of TiO2 exposure on DNA methylation in two cell types, supporting the potential involvement of this epigenetic mechanism in its biological responses. Hence, epigenetic studies are critical for complete assessment of potential risk from exposure.